Índice de calor e desconforto térmico humano nas condições de ambiente natural em Patos, PB, Brasil - Queiroga, Daniel Queiroga (Universidade Federal Rural do Semi-Árido, 2019)
The urban climate in the same way that the interior of the constructions, exercises influence in the man's thermal comfort. In open spaces, the human comfort can be affected by several parameters, among them the climatic ones, the human activities and many studies of thermal comfort are accomplished in internal atmospheres, mainly elaborated by architects, the criteria and the approach used to evaluate the comfort conditions in external atmospheres cannot be the same ones that in internal conditions. The present work had as objective analyzes the Indexes of Heat and Thermal Discomfort, located in the Patos-PB. For the present work, monthly data were analyzed among the years of 2008 and 2018. they were used the software R, with that, we conclude that, the hottest years were 2012 and 2013 with averages of around 35,3 °C, the year with more suave temperature was in 2011 with temperature of 33,77 °C. The average of relative humidity more discharge was in 2009 with percentile of 68,67% and lower average in 2015 and 2017 with 54,23%. The presents data were necessary to make the calculations of the indexes (IDT and IC), such indexes moderate levels of classifications and in agreement with the analyses IDT had maxim and larger lows than 26,5 °C, consisting like this, classification as uncomfortable. Regarding IC he/she had averages between 54,3 °C and 48,23 °C, ending that for levels above 54 °C, it is classified with the level of end danger, taking risk of Cerebral Vascular Accident imminent, and among 41-54 °C it is considered in danger with risks of cramps and heatstroke.
Monografia
Keywords: Temperatura; Umidade; índice de calor e índice de desconforto térmico; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA